Value-focused investigation into programming languages affinity - Neto, Álvaro (2022)
The search for better techniques to teach computer programming is paramount in order to improve the students’ learning experiences. Several approaches have been proposed throughout the years, usually through technical solutions such as evaluation systems, digital classrooms, interactive lessons and so on. Personal factors, such as affinity, have been largely unexplored due to their qualitative and abstract nature. The results of a preliminary survey on how and why affinity is created between programmers and their favorite languages, conducted on a master’s degree class at Universidade do Minho, showed unexpected results as to which languages became favorites and the possible reasons for the students’ choices. Aiming at further exploration on this topic and continuation of this research, the Value-Focused Thinking method was applied in order to construct a more complex, in-depth survey. This value-oriented method kept focus under control and even raised a handful of opportunities to improve the research as a whole. This paper describes the Value-Focused Thinking method and how it was applied to construct a new and deeper computer programming education survey to understand affinity with languages.